Comments on "The optimal supply of public goods and the distortionary cost of taxation" by Louis Kaplow (National Tax Journal, 1996, 513-32) - Dan Usher (Queen's University, Department of Economics, 2004)
An ideal planner would follow the original Samuelson rule to undertake each and every public project, program or activity up to the point where the sum of its marginal benefits is just equal to its marginal cost. Actual governments modify the rule in response to the marginal cost of public funds and the shadow price of public expenditure. The first of these modifications is an additional cost of public revenue, over and above the tax people actually pay, when people rearrange their affairs to minimize their tax bills. The second is the effect - sometimes positive and sometimes negative - of the provision of the public project, program or activity on total tax revenue. Kaplow can be interpreted as arguing that these modifications cancel out, leaving the original Samuelson rule intact. He turns out to be right for public provision of intermediate goods that augment output but do not themselves enter as arguments in the utility function. Otherwise he is mistaken.
Keywords: H21; H41; 330; Public Goods; Deadweight Loss